What Drives the Non-Medical Use of Stimulants Among College Students? The Role of Self-Efficacy and Attitudes: A Cross-Sectional Study of Israeli Undergraduates - Keren Dopelt; Shiran Bord; Nourit Houminer-Klepar (European Journal of Investigation in Health, Psychology and Education)
Background: Non-medical use of prescription stimulants is increasing among college students worldwide. While intended for ADHD treatment, many students use these substances to improve their concentration and academic performance. Despite global research, little is known about the psychological and attitudinal factors influencing such use in the Israeli academic context. Objectives: We wished to examine the relationship between self-efficacy, attitudes toward stimulant use, and actual use among Israeli college students, aiming to uncover the mechanisms behind non-medical stimulant consumption. Methods: A cross-sectional online survey was conducted among 598 students from two Israeli academic institutions. The participants completed validated questionnaires assessing their demographic characteristics, stimulant use patterns, self-efficacy, and attitudes. Results: A total of 22% of students reported using stimulants, 17% of them without a prescription. Positive attitudes significantly increased the likelihood of use (Exp(B) = 3.31, p < 0.001), while higher self-efficacy reduced it (Exp(B) = 0.69, p < 0.01). A negative correlation was found between self-efficacy and favorable attitudes (r = −0.17, p < 0.001). The mediation analysis revealed that self-efficacy influences stimulant use entirely through its effect on attitudes toward stimulants. Additionally, stimulant use was significantly more common among Jewish students (25%) compared to non-Jewish students (11%; p < 0.05) and among smokers (36%) compared to non-smokers (20%; p < 0.001). Conclusions: Positive attitudes and low self-efficacy are key risk factors for stimulant misuse. These findings underscore the need for educational interventions aimed at strengthening self-efficacy and promoting healthier coping strategies in academic settings.